ANALYSIS OF CRIMINAL RESPONSIBILITY AGAINST THE PERPETRATOR CRIMINAL ACTS OF CORRUPTION IN THE USE OF TECHNOLOGY DIGITAL AS A MEANS OF CRIME - Mhd Ihwanuddin Hasibuan; Rahmayanti; Mahadi Siregar (PT. Radja Intercontinental Publishing, 2026)
The rapid development of digital technology has opened up new opportunities for perpetrators of corruption to exploit various digital platforms and systems as a means of committing crimes. This study aims to analyze the forms of criminal liability for perpetrators of corruption who utilize digital technology, review applicable regulations, and formulate comprehensive legal policy recommendations. The research method used is normative juridical with a statutory approach and a conceptual approach. The results show that the use of digital technology in corruption crimes includes the use of virtual accounts, digital cross-border transfers, manipulation of electronic procurement system data, and concealment of assets through crypto assets. Provisions for criminal liability are regulated in Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Criminal Acts of Corruption and Law Number 19 of 2016 concerning Electronic Information and Transactions. The conclusion of this study is that there is a legal gap in handling digital-based corruption that requires comprehensive legislative updates along with strengthening the capacity of law enforcement officers in the field of digital forensics.